The composition of functions f(x) and g(x) where g(x) is acting first is represented by f(g(x)) or (f ∘ g)(x). It combines two or more functions to result in another function. In the composition of functions, the output of one function that is inside the parenthesis becomes the input of the outside function. i.e.,
We can understand this using the following figure:
i.e., to find f(g(x)) (which is read as "f of g of x"), we have to find g(x) first and then we substitute the result in f(x).
The symbol of the composition of functions is ∘. It can also be shown without using this symbol but by using the brackets. i.e.,
Using BODMAS, we always first simplify whatever is within brackets. So to find f(g(x)), first g(x) has to be calculated and is to be substituted within f(x). In the same way, to find g(f(x)), first f(x) has to be calculated and is to be substituted in g(x). i.e., while finding the composite functions, the order matters. It means f(g(x)) may NOT be equal to g(f(x)). For any two functions f(x) and g(x), we find the composite function f(g(a)) using the following steps:
We can understand these steps using the example below. Here we are finding f(g(1)) when f(x) = x^{2}  2x and g(x) = x  5.
We can summarize this process by simple mathematics calculation as shown below:
f(g(1)) = f(15)
= f(6)
= (6)2  2 (6)
= 36 + 12
= 48
To find the composite function of two functions (which are not defined algebraically) shown graphically, we should recall that if (x, y) is a point on a function f(x) then f(x) = y. Using this, to find f(g(a)) (i.e., f(g(x)) at x = a):
Example: Find f(g(5)) from the following graph.
f(g(5)) = f(3) (Because g(5) = 3 as (5, 3) is on g(x))
= 2 (Because f(3) = 2 as (3, 2) is on f(x))
Hence, f(g(5)) = 2.
We have already seen how to find the composite function when a graph of functions is given. Sometimes the points on the graph of functions are shown by tables. So we apply the same procedure as explained in the previous section.
Example: Find g(f(3)) using the following tables.
From the table of f(x), f(3) = 2.
So g(f(3))= g(2).
From the table of g(x), g(2) = 1.
Thus, g(f(3)) = 1.
In general, if g : X → Y and f : Y → Z then f ∘ g : X → Z. i.e., the domain of f ∘ g is X and its range is Z. But when the functions are defined algebraically, here are the steps to find the domain of the composite function f(g(x)).
Example: Find the domain of f(g(x)) when f(x) = 1/(x+2) and g(x) = 1/(x+3).
In f(g(x)), the inner function is g(x) and its domain is A = {x  x ≠ 3}.
Now we will calculate f(g(x)).
Its domain is B = {x : x ≠ 7/2}
Thus, the domain of f(g(x)) is, A ∩ B = {x : x ≠ 3 and x ≠ 7/2}.
This in the interval notation is (∞, 7/2) U (7/2, 3) U (3, ∞).
The range of composite function is calculated just like the range of any other function. It doesn't depend on the inner or outer functions. Let us calculate the range of f(g(x)) that was shown in the last example. We got f(g(x)) = Assume that y = This is a rational function. Hence we solve it for x and set the denominator not equal to zero to find the range.
(2x + 7) y = x + 3
2xy + 7y = x + 3
2xy  x = 3  7y
x (2y  1) = 3  7y
x = (3  7y) / (2y  1)
For range, 2y  1 ≠ 0 which gives y ≠ 1/2.
Therefore, range = {y : y ≠ 1/2}.
406 videos217 docs164 tests


Explore Courses for Class 10 exam
